(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the level of preterm birth, factors predisposing to preterm birth and its outcome during perinatal period. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Obstetrics / Gynae Department, Liaquat Memorial hospital (LMH) Kohat from March 2022 to November 2022. Methods: Weeks of enrolled mother was 28 to 36 in this study, which was assessed from the menstrual period, last period. Clinical record s and ultrasound reports diagnosed the gestational period of the women. Other patients were excluded from the study such as APH, shock and Preeclampsia. Structured questionnaire was used for assessment in this study. Mother also assessed by interview in which face to face contact was used. Hospital record was also used for data collection. SPSS 21 was used for statistical analysis Results: During the study period, 200 patients were included, averaging 21.4±4 years in age. The majority were multigravida (66%), hailing predominantly from rural areas (64%) and possessing a primary education level (51%).Of these participants, about 79% were categorized as late preterm (35-37 weeks gestation), while a quarter reported a history of abortion, and 86% disclosed exposure to spousal smoking. Conclusion: Preterm birth remains a significant public health concern, but it is a challenge that can be addressed through collaborative efforts between healthcare professionals.